Okręg Polesie Armii Krajowej .......... 343 - Dudek, Tomasz (Kresowi żołnierze Armii Krajowej: Historia – Polityka – Pamięć, 2024)
THE HOME ARMY POLESIA DISTRICTThis section discusses the history of the ZWZ-AK (The Home Army Union of Armed Struggle) in its Polesia district during World War Two. In this paper, the author attempted to showcase the operations of individual units of the Polish underground resistance organisation in the Novogrodek area which targeted the Soviets and the Germans, as well as the Ukrainians in the lands adjacent to Volhynia. The author points out a considerable challenge posed to the District Command by the Polesia population density of Poles, which was relatively low and considerably inhibited the efforts of the Polish underground. The author attempted to reconstruct the staffing of individual underground resistance structures in the area. The section culminates in the course of combat operations of the Home Army 30th Infantry Division, and the author’s attempt to showcase the conspiracy operations undertaken by the ZOW (Polish: Związek Obrońców Wolności, Defenders of Freedom), which comprised ex-Home Army operatives and the youth which did not take part in action for Polish independence during the German occupation.